1978
DOI: 10.1128/aac.13.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metronidazole on the Intestinal Microflora of the American Cockroach, Periplaneta americana L

Abstract: The effect of feeding to cockroaches the antimicrobial agent metronidazole, which acts specifically against anaerobes, was assessed by light and scanning electron microscopy, bacteriological examination, and methane formation. Types of organisms and total numbers were greatly reduced from controls. The health of mature adults was unaffected, but stunting occurred in subadult animals maintained on the antibiotic from hatching. The intracellular bacteria of the fat body were not affected by the drug. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 11 publications
3
30
0
1
Order By: Relevance
“…The gut of P. americana contains a dense and morphologically and functionally diverse microbial population contributing to the host development (Bracke et al 1978;Bracke and Markowetz 1980;Gijzen and Barughare 1992;Zurek andKeddie 1996, 1998;Zurek 1998).…”
Section: Introductionmentioning
confidence: 98%
“…The gut of P. americana contains a dense and morphologically and functionally diverse microbial population contributing to the host development (Bracke et al 1978;Bracke and Markowetz 1980;Gijzen and Barughare 1992;Zurek andKeddie 1996, 1998;Zurek 1998).…”
Section: Introductionmentioning
confidence: 98%
“…This hindgut microbial community breaks down recalcitrant dietary components from food that has passed through the fore-and midgut, supplying the cockroach with volatile fatty acids such as acetate (7). While this is not thought to be an obligate symbiosis, reducing the gut microbiota in Periplaneta americana slows development and results in lowered body weight and metabolic activity, suggesting that the gut microbiota plays an important role in the health and fitness of cockroaches (7)(8)(9). Recent work also suggested that the hindgut microbiota is responsible for producing pheromones, including volatile fatty acids, which promote social behavior among cockroaches (10).…”
mentioning
confidence: 99%
“…는데, 진딧물 (Buchner, 1965;Baumann and Baumann, 1994;Munson et al, 1991a), 바퀴벌레 (Bracke et al, 1979), 노린재 (Prado et al, 2006(Prado et al, , 2009 (Munson et al, 1991b;Moran et al, 1993). 따라서 진딧물의 먹이에 tetracycline을 처 리하여 Buchnera균의 생장을 억제하고 제거하였을 때 기주의 생장이 느리고 자손을 생산하지 못하는 것을 보여 주었다 (Mittler, 1971).…”
Section: 일반적으로 곤충들은 절대적 또는 선택적 공생자를 갖게 되unclassified
“…진행되고 있다 (Werren, 1997;Douglas, 1998;Dillon and Dillon, 2004). (Mittler, 1971;Wilkinson, 1998;Koga et al, 2003;Jim and Peter, 2007), 바퀴 (Bracke et al, 1979) Literature Cited…”
Section: 주로 해충을 먹으며 포식성 곤충으로 알려진 무당벌레mentioning
confidence: 99%